2000
DOI: 10.1021/jp000447u
|View full text |Cite
|
Sign up to set email alerts
|

Red Chlorophyll a Antenna States of Photosystem I of the Cyanobacterium Synechocystis sp. PCC 6803

Abstract: The antenna chlorophyll a (Chl a) molecules of photosystem I of green plants and cyanobacteria that absorb further to the red than P700, the special pair of the reaction center, have long been of considerable interest. Recently, the results of nonphotochemical hole burning experiments at liquid helium temperatures, which included use of high pressure and external electric (Stark) fields, led to the conclusion that the cyanobacterium Synechocystis sp. PCC 6803 possesses two "red" antenna states whose S 0 (groun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
94
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(106 citation statements)
references
References 35 publications
12
94
0
Order By: Relevance
“…The pool F699 has its fluorescence emission maximum at 699 nm and was determined by SMS (24). C706 and C714 were proposed based on holeburning spectroscopy and named according to their absorption maxima (26)(27)(28)30). The fluorescence emission maxima for C706 and C714 are expected at Ϸ710 and Ϸ720 nm, respectively (26).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pool F699 has its fluorescence emission maximum at 699 nm and was determined by SMS (24). C706 and C714 were proposed based on holeburning spectroscopy and named according to their absorption maxima (26)(27)(28)30). The fluorescence emission maxima for C706 and C714 are expected at Ϸ710 and Ϸ720 nm, respectively (26).…”
Section: Resultsmentioning
confidence: 99%
“…C706 and C714 were proposed based on holeburning spectroscopy and named according to their absorption maxima (26)(27)(28)30). The fluorescence emission maxima for C706 and C714 are expected at Ϸ710 and Ϸ720 nm, respectively (26). The effect of spectral diffusion differs for these 3 contributions (17,24).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,17 Indeed, at least four red Chl pools were reported: two for LHCI 20 and two for PSI core. 17 It should be emphasized that the spectral parameters obtained and discussed in this contribution cannot be directly compared to those obtained from hole-burning spectroscopy 9,15,16 since it was shown that these two techniques may look selectively at different pools of red Chls in the PSI-LHCI complex. 17 Interestingly, the hole-burning and selective fluorescence studies of red Chls reveal preferentially low-frequency phonons of ∼20 cm -1 and high-frequency phonons of ∼100 cm -1 , respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Additional red Chls pools at 714-715 nm were reported for PSI cores from Synechocystis PCC 6803 and T. elongatus on the basis of hole burning spectroscopy. 9,15,16 Several pools of red Chls were observed in PSI-LHCI complexes from green plants. 4,17 The lowest energy Chls are located in the peripheral antenna, LHCI.…”
Section: Introductionmentioning
confidence: 99%